Marfan’s syndrome: an overview - Yuan, Shi-Min (2010)
Marfan’s syndrome is an autosomal dominant condition with an estimated prevalence of one in 10,000 to 20,000 individuals. This rare hereditary connective tissue disorder affects many parts of the body. The diagnosis of Marfan’s syndrome is established in accordance with a review of the diagnostic criteria, known as the Ghent nosology, through a comprehensive assessment largely based on a combination of major and minor clinical manifestations in various organ systems and the family history. Aortic root dilation and mitral valve prolapse are the main presentations among the cardiovascular malformations of Marfan’s syndrome. The pathogenesis of Marfan’s syndrome has not been fully elucidated. However, fibrillin-1 gene mutations are believed to exert a dominant negative effect. Therefore, Marfan’s syndrome is termed a fibrillinopathy, along with other connective tissue disorders with subtle differences in clinical manifestations. The treatment may include prophylactic β-blockers and angiotensin II-receptor blockers in order to slow down the dilation of the ascending aorta, and prophylactic aortic surgery. Importantly, β-blocker therapy may reduce TGF-β activation, which has been recognized as a contributory factor in Marfan’s syndrome. The present article aims to provide an overview of this rare hereditary disorder.